Fabrication of dual- and single-layer piezoresistive microcantilever sensor - Ab Rahim, Rosminazuin; Bais, Badariah; Yeop Majlis, Burhanuddin (Asian Research Publishing Network (ARPN), 2015)
In this paper, the fabrication of piezoresistive microcantilever (PRM) sensor was realized through the utilization of bulk micromachining technology. Through a sequence of photolithography and etching processes, the device fabrication is realized. The fabrication of two PRM designs, dual-layer and single-layer has opened up the opportunity for device improvement especially in fabrication methods for simpler and reduced process steps. In single-layer design, the fabrication at reduced process steps which offers simpler and reproducible device has been successfully realized. This design offers simpler fabrication process by not only reducing the number of process steps but also eliminating the common fabrication issues encountered in bulk micromachining technology. With the development of single-layer doped silicon PRM sensor, the thermal strain issue, due to mismatch in coefficients of thermal expansion of multi-layered structure is not an issue. The novelty of this work lies in the design itself, in which the single-layer dual leg design not only simplifies the fabrication work, but also promotes an efficient current distribution along the piezoresistive dual-leg structure which is integrated with Wheatstone bridge configuration.